An Alginate/Cyclodextrin Spray Drying Matrix to Improve Shelf Life and Antioxidant Efficiency of a Blood Orange By-Product Extract Rich in Polyphenols: MMPs Inhibition and Antiglycation Activity in Dysmetabolic Diseases. (2nd November 2017) - Lauro, Maria Rosaria; Crascì, Lucia; Giannone, Virgilio; Ballistreri, Gabriele; Fabroni, Simona; Sansone, Francesca; Rapisarda, Paolo; Panico, Anna Maria; Puglisi, Giovanni
Abstract : Alginate and β -cyclodextrin were used to produce easily dosable and spray-dried microsystems of a dried blood orange extract with antidysmetabolic properties, obtained from a by-product fluid extract. The spray-dried applied conditions were able to obtain a concentrate dried extract without the loss of AOA and with TPC and TMA values of 35–40% higher than that of the starting material. They were also effective in producing microparticles with 80–100% of encapsulation efficiency. The 2% sodium alginate was capable of improving the extract shelf life, while the beta-cyclodextrin (1 : 1 molar ratio with dried extract) prolonged the extract antioxidant efficiency by 6 hours. The good inhibition effect of the dried extract on the AGE formation and the MMP-2 and MMP-9 activity is presumably due to a synergic effect exerted by both anthocyanin and bioflavonoid extract compounds and was improved by the use of alginate and cyclodextrin.